Rater reliability and concurrent validity of the Keyboard Personal Computer Style instrument (K-PeCS). - Baker NA; Cook JR; Redfern MS; Baker, Nancy A; Cook, James R; Redfern, Mark S (Applied Ergonomics, 2009)
This paper describes the inter-rater and intra-rater reliability, and the concurrent validity of an observational instrument, the Keyboard Personal Computer Style instrument (K-PeCS), which assesses stereotypical postures and movements associated with computer keyboard use. Three trained raters independently rated the video clips of 45 computer keyboard users to ascertain inter-rater reliability, and then re-rated a sub-sample of 15 video clips to ascertain intra-rater reliability. Concurrent validity was assessed by comparing the ratings obtained using the K-PeCS to scores developed from a 3D motion analysis system. The overall K-PeCS had excellent reliability [inter-rater: intra-class correlation coefficients (ICC)=.90; intra-rater: ICC=.92]. Most individual items on the K-PeCS had from good to excellent reliability, although six items fell below ICC=.75. Those K-PeCS items that were assessed for concurrent validity compared favorably to the motion analysis data for all but two items. These results suggest that most items on the K-PeCS can be used to reliably document computer keyboarding style.